Daily changes in neuronal activities of the dorsal motor nucleus of the vagus under standard and high‐fat diet. (16th June 2021) - Chrobok, Lukasz; Klich, Jasmin D.; Jeczmien‐Lazur, Jagoda S.; Pradel, Kamil; Palus‐Chramiec, Katarzyna; Sanetra, Anna M.; Piggins, Hugh D.; Lewandowski, Marian H.
Abstract : Key points: Recently, we found that the dorsal vagal complex displays autonomous circadian timekeeping properties The dorsal motor nucleus of the vagus (DMV) is an executory part of this complex – a source of parasympathetic innervation of the gastrointestinal tract Here, we reveal daily changes in the neuronal activities of the rat DMV, including firing rate, intrinsic excitability and synaptic input – all of these peaking in the late day Additionally, we establish that short term high‐fat diet disrupts these daily rhythms, boosting the variability in the firing rate, but blunting the DMV responsiveness to ingestive cues These results help us better understand daily control over parasympathetic outflow and provide evidence on its dependence on the high‐fat diet Abstract: The suprachiasmatic nuclei (SCN) of the hypothalamus function as the brain's primary circadian clock, but circadian clock genes are also rhythmically expressed in several extra‐SCN brain sites where they can exert local temporal control over physiology and behaviour. Recently, we found that the hindbrain dorsal vagal complex possesses strong daily timekeeping capabilities, with the area postrema and nucleus of the solitary tract exhibiting the most robust clock properties. The possibility that the executory part of this complex – the dorsal motor nucleus of the vagus (DMV) – also exhibits daily changes has not been extensively studied. The DMV is the source of vagal efferent motoneurons that regulate gastric motility and emptying and consequently influence meal size and energy homeostasis. We used a combination of multi‐channel electrophysiology and patch clamp recordings to gain insight into effects of time of day and diet on these DMV cells. We found that DMV neurons increase their spontaneous activity, excitability and responsiveness to metabolic neuromodulators at late day and this was paralleled with an enhanced synaptic input to these neurons. A high‐fat diet typically damps circadian rhythms, but we found that consumption of a high‐fat diet paradoxically amplified daily variation of DMV neuronal activity, while blunting the neurons responsiveness to metabolic neuromodulators. In summary, we show for the first time that DMV neural activity changes with time of day, with this temporal variation modulated by diet. These findings have clear implications for our understanding of the daily control of vagal efferents and parasympathetic outflow.